DESIGN OF LIBRARY INFORMATION SYSTEM BASED ON FRAMEWORK CODE IGNITER CASE STUDY OF INSTIDLA - Ramadaniah, Dedeh; Fitra, Jaka; Satria, Fiqih; Zidane, El Yazid Gymnastiar (Asia Information System Journal, 2022)
In this disruptive era, information systems are a basic need in every field that we do. Almost all jobs have an information system that is used to help complete the work so that it becomes more effective. Libraries process a lot of data that must be processed properly and quickly so that they can provide maximum service to customers. In addition to the information system built to manage all data, information system security must be a major concern so that data can be stored safely and avoid attacks or defacements from irresponsible people. One way to secure the information system that we create is to separate the model view and controller so that the system will be difficult to hack or disable. With the CodeIgniter Framework, it will be easier for us to create a secure website because CodeIgniter has a Model View Controller (MVC) concept.